Measure of Awareness on Occupational Health and Safety Vulnerability in Technical and Vocational Education and Training Institutions - et. al., Zakir Hussain, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Technical and Vocational Education and Training (TVET) is the future of tomorrow's workforce in the era of the Industrial Revolution 4.0. The ability of TVET institutions to prepare their graduates for future employment is paramount. Graduates who are adequately prepared to adapt to the workplace scenario is very much sought after. Job descriptions may differ slightly from their education and training, but strong fundamentals greatly improve a TVET graduate's employability. Part of this employability is the ability to commit to safety and health processes and procedures in the workplace. A survey using an instrument with a meritorious confirmatory factorial analysis was conducted. The items of the survey try to obtain feedback on awareness among the TVET population. The survey was disseminated using an online survey form. Feedbacks were analyzed using statistical packages to determine the respondents' replies. Utilizing the Pareto analysis, significant items based on respondents' feedback were identified. From the analysis, two hypotheses were formulated, which were then tested using independent samples test to obtain the significant value of the test. From the Pareto analysis, only 40% of the respondents were knowledgeable to assist if there were any safety and health concerns. Further analysis proved that gender did not influence having the knowledge to assist in any safety and health concerns. Additionally, having an industrial experience did not influence having the knowledge to assist in any safety and health concerns. The study on the awareness of occupational health and safety in TVET institutions is still a scarce research topic. By taking into consideration this research study, practical implications focusing on various stakeholders of educational systems; accreditation agencies and government bodies, TVET institutions, and civil society can be further explored and developed. TVET institutions play a pivotal role in providing a competent workforce to industries. The ability to provide experience in handling safety and health concerns within the curriculum can improve TVET graduates’ competency and marketability. However, being a developing country, further research needs to be conducted on safety and health for TVET institutions.